Catalytic Halogen Exchange in Supplementary Activator and Reducing Agent Atom Transfer Radical Polymerization for the Synthesis of Block Copolymers. Issue 4 (2nd December 2020) - De Bon, Francesco; Abreu, Carlos M. R.; Serra, Arménio C.; Gennaro, Armando; Coelho, Jorge F. J.; Isse, Abdirisak A.
Abstract: Synthesis of block copolymers (BCPs) by catalytic halogen exchange ( c HE) is reported, using supplemental activator and reducing agent Atom Transfer Radical Polymerization (SARA ATRP). The c HE mechanism is based on the use of a small amount of a copper catalyst in the presence of a suitable excess of halide ions, for the synthesis of block copolymers from macroinitiators with monomers of mismatching reactivity. c HE overcomes the problem of inefficient initiation in block copolymerizations in which the second monomer provides dormant species that are more reactive than the initiator. Model macroinitiators with low dispersity are prepared and extended to afford well‐defined block copolymers of various compositions. Combined c HE/SARA ATRP is therefore a simple and potent polymerization tool for the copolymerization of a wide range of monomers allowing the production of tailored block copolymers. Abstract : Catalytic halogen exchange overcomes inefficient initiation during block copolymerization when monomers of mismatching reactivity are to be used. Low ppm amounts of selected copper catalysts with suitable excess of chloride ions afford well‐defined block copolymers of various compositions.